1985
DOI: 10.1021/ja00311a108
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectra and bonding in cerocene, bis(.pi.-[8]annulene)cerium(IV)

Abstract: 3(µ3-) group was confirmed by the NMR at 20 °C [ -1.04, septet, 2 3*/(PH) = 4.5, '/(PtH) = 598 Hz] and by the -coupled l95Pt NMR spectra,14 and the presence of CO was confirmed by the IR spectrum [¡-(CO) = 1982 cm"1, cf. ¡-(CO) for 1 = 1750 cm'1].8 At -60 °C the '/(PtH) coupling was reduced to 573 Hz and the chemical shift was -1.47. Further characterization was obtained by treating 3 with 13CO to give 2* (* = 13CO labeled). At -90 °C, the hydride signal was at -1.67 ('/(PtH) = 558 Hz and a doublet splitting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 1 publication
6
110
1
Order By: Relevance
“…31 Opening the capillary and examining the volatile material by 1 H NMR spectroscopy shows it to be free EPR Spectrum and ground state of Ce 2 (cot) 2 . As shown in Figure 5, Ce 2 (cot) 3 has the characteristic spectrum of a spin triplet state with axial symmetry, which is clearly indicated by the present of the half-field peak with g=4.83. 20 The zero-field splitting of g ⊥ disappears as the sample temperature is increased above ~3 K, presumably due to exchange narrowing (see Supporting Information, Figure S1).…”
Section: Synthesis and Physical Properties Of [Li(thf)mentioning
confidence: 83%
See 2 more Smart Citations
“…31 Opening the capillary and examining the volatile material by 1 H NMR spectroscopy shows it to be free EPR Spectrum and ground state of Ce 2 (cot) 2 . As shown in Figure 5, Ce 2 (cot) 3 has the characteristic spectrum of a spin triplet state with axial symmetry, which is clearly indicated by the present of the half-field peak with g=4.83. 20 The zero-field splitting of g ⊥ disappears as the sample temperature is increased above ~3 K, presumably due to exchange narrowing (see Supporting Information, Figure S1).…”
Section: Synthesis and Physical Properties Of [Li(thf)mentioning
confidence: 83%
“…29 The TIP value of 1.7(2) × 10 -4 emu/mol compares well with the published value of 1.4(2) × 10 -4 emu/mol using Pascal´s constants. Thermal conversion of Ce(cot) 2 to Ce 2 (cot) 3 . Unlike Th(cot) 2 , which sublimes at 135-160 °C in vacuum, 27,30,31 and U(cot) 2 , which sublimes at 140-210 °C in vacuum, 26,32,33 cerocene does not sublime when heated under diffusion pump vacuum.…”
Section: Synthesis and Physical Properties Of [Li(thf)mentioning
confidence: 99%
See 1 more Smart Citation
“…In [Ln n -(COT) n+1 ], however, an orbital contributing to the ionization process is considered to be discontinuously localized along the molecular axis, because the cluster is bonded through ionic bonds and the charge is localized at each component. Since the first ionization is expected to occur from 4f (Ln) orbitals in (1, 2), 79,80 it is concluded that 4f orbital in the cluster is localized and scarcely interacts with neighboring Ln atoms in the cluster. According to the theoretical calculation of Dolg and co-workers, 74c [Nd(COT) 2 ] is a charge-transfer complex in which 3 of 6 electrons in Nd(6s 2 4f 4 ) transfer almost completely to 2COT, resulting in a configuration of Nd 3+ (COT 1.5¹ ) 2 .…”
Section: Ionization Energies Of Neutral Ln N (Cot) N+1mentioning
confidence: 99%
“…Since COT 2¹ takes 10³ electronic configuration with the e 2u HOMO as shown in the inset of Figure 7, two ligands of COT 2¹ form two high-lying MOs of e 2u and e 2g with the level ordering e 2u > e 2g . 79,80 Then, the bands of X and A are undoubtedly associated with electron detachment from the highest occupied molecular orbital (HOMO; e 2u ) and the HOMO¹1 (e 2g ) molecular orbitals, respectively. …”
mentioning
confidence: 99%